Detection of an IMI-2 carbapenemase-producing Enterobacter asburiae at a Swedish feed mill - Börjesson, Stefan; Brouwer, Michael S. M.; Östlund, Emma; Eriksson, Jenny; Elving, Josefine; Karlsson Lindsjö, Oskar; Engblom, Linda I. (Frontiers in Microbiology, 2022)
Occurrence of multi-drug-resistant Enterobacteriaceae in livestock is of concern as they can spread to humans. A potential introduction route for these bacteria to livestock could be animal feed. We therefore wanted to identify if Escherichia spp., Enterobacter spp., Klebsiella spp, or Raoutella spp. with transferable resistance to extended-cephalosporins, carbapenems or colistin could be detected in the environment at feed mills in Sweden. A second aim was to compare detected isolates to previous described isolates from humans and animals in Sweden to establish relatedness which could indicate a potential transmission between sectors and feed mills as a source for antibiotic resistant bacteria. However, no isolates with transferable resistance to extended-cephalosporins or colistin could be identified, but one isolate belonging to the Enterobacter cloacae complex was shown to be carbapenem-resistant and showing carbapenemase-activity. Based on sequencing by both short-read Illumina and long-read Oxford Nanopore MinIon technologies it was shown that this isolate was an E. asburiae carrying a blaIMI-2 gene on a 216 Kbp plasmid, designated pSB89A/IMI-2, and contained the plasmid replicons IncFII, IncFIB, and a third replicon showing highest similarity to the IncFII(Yp). In addition, the plasmid contained genes for various functions such as plasmid segregation and stability, DNA, plasmid transfer and arsenical transport, but no additional antibiotic resistance genes. This isolate and the pSB89A was compared to three human clinical isolates positive for blaIMI-2 available from the Swedish antibiotic monitoring program Swedres. It was shown that one of the human isolates carried a plasmid similar with regards to gene content to the pSB89A/IMI-2 except for the plasmid transfer system, but that the order of genes was different. The pSB89A/IMI-2 did however share the same transfer system as the blaIMI-2 carrying plasmids from the other two human isolates. The pSB89A/IMI-2 was also compared to previously published plasmids carrying blaIMI-2, but no identical plasmids could be identified. However, most shared part of the plasmid transfer system and DNA replication genes, and the blaIMI-2 gene was located next the transcription regulator imiR. The IS3-family insertion element downstream of imiR in the pSB89A was also related to the IS elements in other blaIMI-carrying plasmids.